A student perspective of academic integrity - Sanni-Anibire, Hafizat (Canadian Perspectives on Academic Integrity, 2021)
<span class="NormalTextRun SCXW257033860 BCX9" data-ccp-charstyle="normaltextrun" data-ccp-charstyle-defn=""ObjectId":"8b1803d7-86ed-4f01-8514-f22dff170ec8|55","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"normaltextrun",469778129,"normaltextrun",469778324,"Default Paragraph Font"]">My presentation will be about my perspectives of academic integrity as it is presented at my university, and the challenges I believe it may pose to students. Beginning with my previous experiences as a student outside of Canada, then as a foreign student in Canada, and my current involvement with academic integrity, including the lessons I learnt from a recent academic integrity research project, I will share ways in which I believe post-secondary institutions, faculty and resource staff may improve students’ experiences and understanding of academic integrity as separate and different from misconduct. I will also share suggestions for involving students in the conversation around academic integrity.<span class="NormalTextRun SCXW257033860 BCX9" data-ccp-charstyle="eop" data-ccp-charstyle-defn=""ObjectId":"8b1803d7-86ed-4f01-8514-f22dff170ec8|56","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"eop",469778129,"eop",469778324,"Default Paragraph Font"]">